Impact of post-transplantation maintenance therapy on health-related quality of life in patients with multiple myeloma: data from the Connect® MM Registry - Abonour, Rafat (Ann Hematol, 2018)
Maintenance therapy after autologous stem cell transplantation (ASCT) is recommended for use in multiple myeloma (MM); however, more data are needed on its impact on health-related quality of life (HRQoL). Presented here is an analysis of HRQoL in a Connect MM registry cohort of patients who received ASCT ± maintenance therapy. The Connect MM Registry is one of the earliest and largest, active, observational, prospective US registry of patients with symptomatic newly diagnosed MM. Patients completed the Functional Assessment of Cancer Therapy-MM (FACT-MM) version 4, EuroQol-5D (EQ-5D) questionnaire, and Brief Pain Inventory (BPI) at study entry and quarterly thereafter until death or study discontinuation. Patients in three groups were analyzed: any maintenance therapy (n = 244), lenalidomide-only maintenance therapy (n = 169), and no maintenance therapy (n = 137); any maintenance and lenalidomide-only maintenance groups were not mutually exclusive. There were no significant differences in change from pre-ASCT baseline between any maintenance (P = 0.60) and lenalidomide-only maintenance (P = 0.72) versus no maintenance for the FACT-MM total score. There were also no significant differences in change from pre-ASCT baseline between any maintenance and lenalidomide-only maintenance versus no maintenance for EQ-5D overall index, BPI, FACT-MM Trial Outcomes Index, and myeloma subscale scores. In all three groups, FACT-MM, EQ-5D Index, and BPI scores improved after ASCT; FACT-MM and BPI scores deteriorated at disease progression. These data suggest that post-ASCT any maintenance or lenalidomide-only maintenance does not negatively impact patients’ HRQoL. Additional research is needed to verify these findings. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00277-018-3446-y) contains supplementary material, which is available to authorized users.